A novel Wim Hof psychophysiological training program to reduce stress responses during an Antarctic expedition - Tereza Petraskova Touskova (Journal of International Medical Research, 2022)
Objective The aim of this prospective observational study was to investigate the effects of a novel Wim Hof psychophysiological training program on stress responses and hormone release in healthy participants during an Antarctic expedition. Methods All members of an Antarctic expedition were included in the study. The participants were healthy volunteers allocated to an intervention group (n = 6) and a control group (n = 7). The intervention consisted of 8 weeks of Wim Hof training. The training program comprised three integrated parts: breathing exercises, cold exposure and meditation. Psychometric measures (the Beck Depression Inventory and the Trauma Symptom Checklist-40) and neuroendocrine measures (cortisol, melatonin) were assessed pre- and post-intervention. Results The results showed that the 8-week training program significantly reduced stress responses, as indicated by a reduction in depressive symptoms. A non-significant reduction in cortisol was also observed. Conclusions These data constitute preliminary findings indicating that the Wim Hof Method may positively affect stress symptoms and adaptability of the hormonal system to respond adequately to the circadian rhythm in healthy volunteers who participated in an Antarctic expedition.